Complete Chloroplast Genome of Nicotiana otophora and its Comparison with Related Species - Asaf, Sajjad; Khan, Abdul L.; Khan, Abdur R.; Waqas, Muhammad; Kang, Sang-Mo; Khan, Muhammad A.; Lee, Seok-Min; Lee, In-Jung (Frontiers in Plant Science, 2016)
Nicotiana otophora is a wild parental species of Nicotiana tabacum, an interspecific hybrid of N. tomentosiformis and N. sylvestris. However, N. otophora is least understood as an alternative paternal donor. Here, we compared the fully assembled chloroplast (cp) genome of N. otophora and with those of closely related species. The analysis showed a cp genome size of 156,073 bp and exhibited a typical quadripartite structure, which contains a pair of inverted repeats separated by small and large single copies, containing 163 representative genes, with 165 microsatellites distributed unevenly throughout the genome. Comparative analysis of a gene with known function across Nicotiana species revealed 76 protein-coding sequences, 20 tRNA sequences, and 3 rRNA sequence shared between the cp genomes. The analysis revealed that N. otophora is a sister species to N. tomentosiformis within the Nicotiana genus, and Atropha belladonna and Datura stramonium are their closest relatives. These findings provide a valuable analysis of the complete N. otophora cp genome, which can identify species, elucidate taxonomy, and reconstruct the phylogeny of genus Nicotiana.